Strategi dan Implementasi Kampanye ABWA 3.0: Meningkatkan Literasi Finansial Remaja melalui Aplikasi Campaign #ForChange di PT Uni Tokopo Teknologi - Maulidya Rintalla; Wahyu Fahrul Ridho (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
The ABWA 3.0 campaign utilizes the Campaign.com app to connect individuals, communities, and sponsors concerned about social issues. Through the Campaign #ForChange app, social organizations engage young generations, providing education and fostering action on specific social issues. The app enables online campaigns supported by private sector sponsors, with donations from completed social challenges. It features a transparent donation tracker, showcasing collective efforts. Social campaign topics are determined collaboratively. Research from credible sources informs problem-solving. The campaign process involves mentor-guided exploration and group assignments, with progress reports tracking tasks. The campaign aims to address the urgent issue of financial literacy among Indonesian youth. Root causes include a lack of financial education and the need for support from schools and homes. This research aims to strategize and implement the ABWA 3.0 campaign, promoting financial literacy through the Campaign #ForChange app at PT Uni Tokopo Teknologi.